Oral Fusobacterium nucleatum exacerbates ulcerative colitis via the oral-gut axis: mechanisms and therapeutic implications - Zheng, Zhaoyu; Jin, Wenqin; Guo, Weiwei; Jin, Zhao; Zuo, Yuling (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundFusobacterium nucleatum (F. nucleatum) is an anaerobic bacterium known for its association with periodontal disease and oral infections. It has been implicated in the development of gastrointestinal diseases such as inflammatory bowel disease and colorectal cancer. Ulcerative colitis (UC), which is characterized by chronic inflammation of the colon, is a condition of unknown etiology with a rising incidence rate, significantly affecting the quality of life for patients. The increased intestinal permeability during UC may facilitate the adherence or invasion of F. nucleatum into the damaged intestinal barrier, leading to exacerbated inflammation.MethodsThis article introduces the concept of the oral-gut axis, reviewing existing literature to analyze the role of F. nucleatum in the pathogenesis of UC and exploring its potential pathogenic mechanisms. It also summarizes the latest advances in treating patients with UC who have F. nucleatum and looks forward to prospective therapeutic strategies and the translational prospects of F. nucleatum within the oral-gut axis.ResultsF. nucleatum may be a key player in the pathogenesis of UC, likely due to its invasiveness during periods of increased intestinal permeability. The paper also discusses innovative approaches for the prevention and management of UC exacerbated by F. nucleatum, paving the way for more effective treatment of UC.ConclusionThe review offers new insights into the complex relationship between the oral microbiome and intestinal diseases, enhancing our understanding of their dynamic interactions. There is a paucity of literature on therapeutic approaches, indicating a need for further clinical research.